2012
DOI: 10.1007/s10571-012-9814-6
|View full text |Cite
|
Sign up to set email alerts
|

What can We Know from Pituitary–Adrenal Hormones About the Nature and Consequences of Exposure to Emotional Stressors?

Abstract: Exposure to stress induces profound physiological and behavioral changes in the organisms and some of these changes may be important regarding stress-induced pathologies and animal models of psychiatric diseases. Consequences of stress are dependent on the duration of exposure to stressors (acute, chronic), but also of certain characteristics such as intensity, controllability, and predictability. If some biological variables were able to reflect these characteristics, they could be used to predict negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 62 publications
2
42
0
1
Order By: Relevance
“…However, the magnitude of the effect is dependent on the severity and length of exposure to the stressors (see Armario et al, 2008 for a review). Results from our lab show that after an acute exposure to IMO a long-term endocrine and/or behavioural sensitization to novel environments can develop, but both phenomena appear to be dissociated (Belda et al, 2008(Belda et al, , 2012Gagliano et al, 2008;Muñoz-Abellán et al, 2008).…”
Section: Endocrine Responsementioning
confidence: 84%
“…However, the magnitude of the effect is dependent on the severity and length of exposure to the stressors (see Armario et al, 2008 for a review). Results from our lab show that after an acute exposure to IMO a long-term endocrine and/or behavioural sensitization to novel environments can develop, but both phenomena appear to be dissociated (Belda et al, 2008(Belda et al, , 2012Gagliano et al, 2008;Muñoz-Abellán et al, 2008).…”
Section: Endocrine Responsementioning
confidence: 84%
“…They include biotic factors such as food availability, the presence of predators, infection with pathogenic organisms or interactions with conspecifics, as well as abiotic factors such as temperature, water availability and toxicants. In addition, psychological and emotional stressors, which involve perceived threats, are extremely important in humans and other mammals (Armario et al, 2012;Campbell and Ehlert, 2012), and they are likely important in other animals as well (Galhardo and Oliveira, 2009). Organisms respond to stressors by mounting a stress response that involves a complex set of behavioural and physiological changes at multiple levels of biological organization.…”
Section: Reviewmentioning
confidence: 99%
“…The focus of the field of stress biology on these hormonal mechanisms has been such that glucocorticoid release is often treated as the key indicator of the occurrence of stress in vertebrates (Armario et al, 2012;Campbell and Ehlert, 2012), and the term 'stress response' is often treated as synonymous with the glucocorticoid-mediated stress response. While this greatly simplifies the detection of stress, because these hormones are easily quantified, it is not clear that this definition of stress is sufficiently broad as to encompass all situations.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…For example, many studies have shown that social defeat, in which an individual loses a competitive contest with a rival, induces a wide variety of both transient and persistent detrimental and compensatory physiological changes consistent with stress-responses in a variety of vertebrates (see Buwalda et al, 2005;Hostetler and Ryabinin, 2013 for general reviews), including birds (e.g., Zuk and Johnsen, 2000;Carere et al, 2001Carere et al, , 2003Gleeson, 2006;Hawley, 2006;Hawley et al, 2006). Different sources and kinds of stressors can yield dramatically different physiological responses, involving a variety of pathways, neurotransmitters, and target tissues (Buchanan, 2000;Armario et al, 2012;Hostetler and Ryabinin, 2013). Therefore, it is possible that stress-responses resulting from social interactions may manifest differently than stress-responses derived from other sources, in which case certain dynamic signals could be influenced more by social experience than by other physiological perturbations.…”
Section: Introductionmentioning
confidence: 99%